Collaborative governance in program implementation fish apartment in east luwu - Jeri Mahjud; Thahir Haning; Suryadi Lambali; Nurul Mufidah (LEGAL BRIEF, 2023)
The fish apartment program is a program that collaborates with various stakeholders in the context of restoring fish habitat and increasing fishermen's catches. This research aims to determine the collaborative governance of the community empowerment program through fish apartments at east luwu regency. The research used a qualitative research method with a descriptive type. The data was collected through in-depth interviews, observation, and documentation. Data were analyzed using an interaction analysis model by (Miles & Huberman, 1994) with data collection, data condensation, data display, and conclusion drawing/verifying. The results of the study show that collaborative governance in the community empowerment program through the fish apartment in Malili District, East Luwu Regency uses the collaborative governance approach of (Ansell & Gash, 2008), namely (1) Face-to-face dialogue running well, this can be seen during coordination meetings either through internal coordination of each party, as well as coordination meetings that include all collaborating parties. (2) Building trust has not been well established, this is due to the trust of the government and the community towards PT. Vale is less intertwined due to the long disbursement process and lack of transparency. (3) Commitment to the process has been carried out well, this can be seen from the participation of all parties, government, private, and civil society in the planning process to program implementation. (4) Shared understanding has been carried out well, through outreach which discussed the common goal of creating a fish apartment program. (5) Intermediate outcomes of the fish apartment building program have had a positive impact on the marine ecosystem, this can be seen from the large number of fish that have gathered around the fish apartments which have been lowered to the seabed